Anti-racist scholar-activism - Joseph-Salisbury, Remi; Connelly, Laura (Book collections on Project MUSE., 2022)
This book focuses on anti-racist scholar-activism in the margins of universities in the United Kingdom. The book raises questions about the future of Higher Education in the UK, and shines a spotlight on those academics who are working within, and often against, their institutions. Through the accounts of participants, the authors argue that another university is not only possible, but is essential. Working towards a 'manifesto' for scholar-activism in the book's conclusion, the book explores a range of concepts that might be thought to guide scholar-activism, including 'reparative theft', 'working in service', 'digging where you stand', and 'constructive complicity'. Throughout, the authors show 'scholar-activism' to be something that is complex and multifaceted, and better thought of as a form of practice, rather than an identity that can be attained.